2015
DOI: 10.1016/j.bbamcr.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A guide to mechanobiology: Where biology and physics meet

Abstract: Cells actively sense and process mechanical information that is provided by the extracellular environment to make decisions about growth, motility and differentiation. It is important to understand the underlying mechanisms given that deregulation of the mechanical properties of the extracellular matrix (ECM) is implicated in various diseases, such as cancer and fibrosis. Moreover, matrix mechanics can be exploited to program stem cell differentiation for organ-on-chip and regenerative medicine applications. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
207
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(220 citation statements)
references
References 197 publications
3
207
1
9
Order By: Relevance
“…Some of these molecules are implicated in numerous pathways eventually dictating cell fate and functions. 4,5 Adhesion dynamics profoundly affects the RhoA/ROCK pathway, whose activity regulates the osteogenic/adipogenic fate of MSCs. 51 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 28 Cell-generated contractility might also impact at the transcriptional level directly.…”
Section: Effects Of Materials Features On Adhesion Proliferation and Mmentioning
confidence: 99%
“…Some of these molecules are implicated in numerous pathways eventually dictating cell fate and functions. 4,5 Adhesion dynamics profoundly affects the RhoA/ROCK pathway, whose activity regulates the osteogenic/adipogenic fate of MSCs. 51 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 28 Cell-generated contractility might also impact at the transcriptional level directly.…”
Section: Effects Of Materials Features On Adhesion Proliferation and Mmentioning
confidence: 99%
“…It is well recognized that beside biochemical input, the mechanical characteristics of a cell's environment can have a profound influence on its biological properties [3][4][5] . Neuronal and glial cells are sensitive to mechanical input during development, in disease and regenerative states [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Exciting experiments in the field of mechanobiology have demonstrated that molecules, cells, and tissues are able to sense their environments and respond biologically to mechanical signals (1). Mechanical force is sensed by loadinduced changes in the conformation and/or activities of mechanosensitive macromolecules (i.e., mechanosensors), which in turn lead to a biological response.…”
mentioning
confidence: 99%